Empowering smart cities: Unlocking citizen participation through AI-driven personalization and perceived value - Afshar Hatami; Somayyeh Naseramini Jeloudarlou; Haniyeh Asadzadeh (Sustainable Futures)
This study grounded in perceived value theory, examines a notable gap in the literature on the mediation role of citizen's perceived value (CPV) between AI-driven personalization (AI-DP) and citizens participation (CP). The research method is descriptive-survey, and the data collection tool is a standard and online questionnaire. The statistical population includes citizens of the Tehran metropolis in Iran who have used the smart services of My Tehran app at least once in various urban areas. Structural equation modeling with AMOS 26 is used to test the hypotheses. The empirical results showed that AI-DP enhances CP in service delivery by modifying services to citizens preferences and increasing relevance and quality of services offered. CPV also acts as a partial mediator in this relationship, meaning the citizens' perception of usefulness, transparency, and quality of services is very important in forming an opinion toward personalization with active participation. This study closes the gap in the literature by integrating both the technological perspective as well as the behavioral perspective and hence provides some invaluable suggestions to urban policymakers and developers of smart services. The findings indicate that smart urban governance can be responsive and participative if AI systems are designed in a user-centered approach that meets the needs of citizens to ensure an enhanced level of trust and participation among the public.